Epidemiology, neurobiology and pharmacological interventions related to suicide deaths and suicide attempts in bipolar disorder: Part I of a report of the International Society for Bipolar Disorders Task Force on Suicide in Bipolar Disorder. (September 2015) - Schaffer, Ayal; Isometsä, Erkki T; Tondo, Leonardo; Moreno, Doris H; Sinyor, Mark; Kessing, Lars Vedel; Turecki, Gustavo; Weizman, Abraham; Azorin, Jean-Michel; Ha, Kyooseob; Reis, Catherine; Cassidy, Frederick; et al.
Objectives: Bipolar disorder is associated with elevated risk of suicide attempts and deaths. Key aims of the International Society for Bipolar Disorders Task Force on Suicide included examining the extant literature on epidemiology, neurobiology and pharmacotherapy related to suicide attempts and deaths in bipolar disorder. Methods: Systematic review of studies from 1 January 1980 to 30 May 2014 examining suicide attempts or deaths in bipolar disorder, with a specific focus on the incidence and characterization of suicide attempts and deaths, genetic and non-genetic biological studies and pharmacotherapy studies specific to bipolar disorder. We conducted pooled, weighted analyses of suicide rates. Results: The pooled suicide rate in bipolar disorder is 164 per 100, 000 person-years (95% confidence interval = [5, 324]). Sex-specific data on suicide rates identified a 1.7:1 ratio in men compared to women. People with bipolar disorder account for 3.4–14% of all suicide deaths, with self-poisoning and hanging being the most common methods. Epidemiological studies report that 23–26% of people with bipolar disorder attempt suicide, with higher rates in clinical samples. There are numerous genetic associations with suicide attempts and deaths in bipolar disorder, but few replication studies. Data on treatment with lithium or anticonvulsants are strongly suggestive for prevention of suicide attempts and deaths, but additional data are required before relative anti-suicide effects can be confirmed. There were limited data on potential anti-suicide effects of treatment with antipsychotics or antidepressants. Conclusion: This analysis identified a lower estimated suicide rate in bipolar disorder than what was previously published. Understanding the overall risk of suicide deaths and attempts, and the most common methods, are important building blocks to greater awareness and improved interventions for suicide prevention in bipolar disorder. Replication of genetic findings and stronger prospective data on treatment options are required before more decisive conclusions can be made regarding the neurobiology and specific treatment of suicide risk in bipolar disorder.